The Representative Illocutionary Acts in Diana Character of The Wonder Woman Movie (2017) - Muziatun, Muziatun; Bay, Indri Wirahmi; Mukmin, Rara Sinta (Ideas Publishing, 2025)
This study was conducted to explain and find out what are the types of representative illocutionary acts used by Diana in the film Wonder Woman (2017). with the aim that readers can understand the use of speech when communicating with others. the method used in this film is descriptive qualitative method, because qualitative research is research that involves analyzing and interpreting texts. According to Searle (1979), representative speech acts are speech acts in which speakers are involved in conveying the truth of a proposition, such as by providing information, making recommendations, explaining, and so on. Diana from the movie is the subject of the research and her various representative illocutionary acts are the data for this research. This study found 12 speech acts from Diana speech. and the most dominant ones found are 6 speech acts to informing, 4 each to asserting, convincing, and 4 to refuting. it can be concluded that the 12 dominant speech acts used are informing, asserting, convincing, and refuting.